MEASURING THE SUCCESS OF THE LECTURER E-PERFORMANCE APPLICATION AT BUNG HATTA UNIVERSITY - Ice Kamela; Zeshasina Rosha; Rika Desiyanti; Afifah Windi; Irda - (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Information system used at Bung Hatta University uses Digital Campus, one of the applications is E-Lecturer Performance . E- Performance Applications Lecturer designed For manage related data academic covers teaching , research , supporting , PKM, journals, proceedings , books , IPR and recognition use technology computer . Quality information system helps give satisfaction for University And lecturers in improving Power compete , give mark plus for University. To measure success something The Lecturer E-Performance application that already exists on the Bung Hatta University website and has been used by lecturers, needs to be evaluated by measuring the level of success of the application by apply model of success Delone And McLean , the analysis method used is descriptive analysis which is based on the actual scores from respondents' answers, while the number of samples used was 95 respondents. The results explain that the application as a whole has a very good running system quality with a score of 95.01%. Meanwhile, the hypothesis results from 10 hypotheses, there are 6 hypotheses accepted and 4 hypotheses rejected and the role of mediating variables can be partial and full mediation so that the findings from this research are that system quality has a very significant effect on user satisfaction